O profissional da educação e a Indústria 4.0: mapeamento de competências para profissionais da educação na perspectiva da Indústria 4.0 - Soares, Daniela de Meireles (2022)
This research aimed to map the skills needed by education professionals in the perspective of Industry 4.0. For this, a literature review was carried out in the first part of the work, seeking concepts from researchers in the area to contextualize Industry 4.0, skills trends, education 4.0, as well as to present some possibilities of technologies that make up Industry 4.0 in education and brief reflection on education professionals, in the perspective of the New Revolution. In the second part of the research, a systematic literature review was planned to use the Web of Science and Scopus databases, considered highly relevant scientific document platforms, after analyzing the collected documents, 13 articles were chosen that met the research objectives. For the most part, the documents understood as education professional, only teachers, however, it is worth mentioning that in an educational institution there is a team of various education professionals, who work together and who must, like the teachers, qualify and seek to acquire the new skills required for the context of the new revolution. In total, 43 competencies and skills aimed at educators were found, the most cited being: Growth mindset, adaptability, continuous learning ability, critical thinking, complex problem solving, communication, creativity and as the most cited digital and technological competence. However, it is concluded that Education has a fundamental role in this new revolution, forming qualified individuals to be inserted in a context that is still under construction, but which will undoubtedly be a complete reality in the future, for which professionals who are inserted in educational environments need more than ever, seek to acquire the necessary skills and abilities required for this new 4.0 era.